RETRACTED ARTICLE: The anti-osteosarcoma property of ailanthone through regulation of miR-126/VEGF-A axis. Issue 1 (4th December 2019) - Kong, Daliang; Ying, Boda; Zhang, Jinrui; Ying, Hongliang
Abstract: We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Daliang Kong, Boda Ying, Jinrui Zhang & Hongliang Ying (2019) The anti-osteosarcoma property of ailanthone through regulation of miR-126/VEGF-A axis. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 3913-3919, DOI: 10.1080/21691401.2019.1669622 Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to provide their original data or to fully respond to our questions regarding the process of the research conducted. Therefore, the authors have agreed to the retraction of the article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.